TEACHING SURFACE MEASUREMENT UNITS TO ELEMENTARY SCHOOL STUDENTS - Bozorov, Murot Nashvandovich (Fakultas Ilmu Pendidikan, Universitas Persatuan Guru Republik Indonesia Semarang, 2024)
Mathematics learning needs to be taught to elementary school children because they will encounter various mathematical problems in their daily lives. The aim of this research is to describe surface material mathematics learning in elementary school children in grades 1 and 2 in Uzbekistan. This research is phenomenological research where researchers describe real situations in the field and report them scientifically. The data collection method used is observation. The results of the research show that teaching surface material mathematics in grades 1 and 2 of elementary schools in Uzbekistan is carried out using the drill/drilling method where the teacher gives students various problems about various types of surfaces. The conclusion obtained from this research is that the drilling method is able to make teachers successful in teaching surface material to students in grades 1 and 2 in elementary schools in Uzbekistan